In-cell bioluminescence resonance energy transfer (BRET)-based assay uncovers ceritinib and CA-074 as SARS-CoV-2 papain-like protease inhibitors - Mei Li; Zhu-Chun Bei; Yongtian Yuan; Baogang Wang; Dongna Zhang; Likun Xu; Liangliang Zhao; Qin Xu; Yabin Song (Taylor & Francis Group, 2024)
Papain-like protease (PLpro) is an attractive anti-coronavirus target. The development of PLpro inhibitors, however, is hampered by the limitations of the existing PLpro assay and the scarcity of validated active compounds. We developed a novel in-cell PLpro assay based on BRET and used it to evaluate and discover SARS-CoV-2 PLpro inhibitors. The developed assay demonstrated remarkable sensitivity for detecting the reduction of intracellular PLpro activity while presenting high reliability and performance for inhibitor evaluation and high-throughput screening. Using this assay, three protease inhibitors were identified as novel PLpro inhibitors that are structurally disparate from those previously known. Subsequent enzymatic assays and ligand-protein interaction analysis based on molecular docking revealed that ceritinib directly inhibited PLpro, showing high geometric complementarity with the substrate-binding pocket in PLpro, whereas CA-074 methyl ester underwent intracellular hydrolysis, exposing a free carboxyhydroxyl group essential for hydrogen bonding with G266 in the BL2 groove, resulting in PLpro inhibition.